Hypoxia and renal fibrosis - Naas, Stephanie; Schiffer, Mario; Schödel, Johannes (American Journal of Physiology-Cell Physiology, 2023)
Renal fibrosis is the final stage of most progressive kidney diseases. Chronic kidney disease (CKD) is associated with high comorbidity and mortality. Thus, preventing fibrosis and thereby preserving kidney function increases the quality of life and prolongs the survival of patients with CKD. Many processes such as inflammation or metabolic stress modulate the progression of kidney fibrosis. Hypoxia has also been implicated in the pathogenesis of renal fibrosis, and oxygen sensing in the kidney is of outstanding importance for the body. The dysregulation of oxygen sensing in the diseased kidney is best exemplified by the loss of stimulation of erythropoietin production from interstitial cells in the fibrotic kidney despite anemia. Furthermore, hypoxia is present in acute or chronic kidney diseases and may affect all cell types present in the kidney including tubular and glomerular cells as well as resident immune cells. Pro- and antifibrotic effects of the transcription factors hypoxia-inducible factors 1 and 2 have been described in a plethora of animal models of acute and chronic kidney diseases, but recent advances in sequencing technologies now allow for novel and deeper insights into the role of hypoxia and its cell type-specific effects on the progression of renal fibrosis, especially in humans. Here, we review existing literature on how hypoxia impacts the development and progression of renal fibrosis.
CRIS-Team Scopus Importer:2024-05-13
Keywords: chronic kidney disease; HIF; hypoxia; hypoxia-inducible factors; renal fibrosis

Hypoxia controls expression of kidney-pathogenic MUC1 variants - Naas, Stephanie; Krüger, René; Knaup, Karl; Naas, Julia; Grampp, Steffen; Schiffer, Mario; Wiesener, Michael; Schödel, Johannes (Life Science Alliance, 2023)
The interplay between genetic and environmental factors influences the course of chronic kidney disease (CKD). In this context, genetic alterations in the kidney disease gene MUC1 (Mucin1) predispose to the development of CKD. These variations comprise the polymorphism rs4072037, which alters splicing of MUC1 mRNA, the length of a region with variable number of tandem repeats (VNTR), and rare autosomal-dominant inherited dominant-negative mutations in or 59 to the VNTR that causes autosomal dominant tubulointerstitial kidney disease (ADTKD-MUC1). As hypoxia plays a pivotal role in states of acute and chronic kidney injury, we explored the effects of hypoxia-inducible transcription factors (HIF) on the expression of MUC1 and its pathogenic variants in isolated primary human renal tubular cells. We defined a HIF-binding DNA regulatory element in the promoter-proximal region of MUC1 from which hypoxia or treatment with HIF stabilizers, which were recently approved for an anti-anemic therapy in CKD patients, increased levels of wild-type MUC1 and the disease-associated variants. Thus, application of these compounds might exert unfavorable effects in patients carrying MUC1 risk variants.
CRIS-Team Scopus Importer:2023-08-11

Hypoxia hits APOL1 in the kidney - Grampp, Steffen; Krüger, René; Lauer, Victoria; Uebel, Sebastian; Knaup, Karl; Naas, Julia; Höffken, Verena; Weide, Thomas; Schiffer, Mario; Naas, Stephanie; Schödel, Johannes (Kidney International, 2023)
Individuals of African ancestry carrying two pathogenic variants of apolipoprotein 1 (APOL1) have a substantially increased risk for developing chronic kidney disease. The course of APOL1 nephropathy is extremely heterogeneous and shaped by systemic factors such as a response to interferon. However, additional environmental factors operating in this second-hit model have been less well defined. Here, we reveal that stabilization of hypoxia-inducible transcription factors (HIF) by hypoxia or HIF prolyl hydroxylase inhibitors activates transcription of APOL1 in podocytes and tubular cells. An active regulatory DNA-element upstream of APOL1 that interacted with HIF was identified. This enhancer was accessible preferentially in kidney cells. Importantly, upregulation of APOL1 by HIF was additive to the effects of interferon. Furthermore, HIF stimulated expression of APOL1 in tubular cells derived from the urine of an individual carrying a risk variant for kidney disease. Thus, hypoxic insults may serve as important modulators of APOL1 nephropathy.
CRIS-Team Scopus Importer:2023-05-26
Keywords: chronic kidney disease; hypoxia; podocyte; transcription regulation

Hypoxia induces polycystin-1 expression in the renal epithelium - Grampp, Steffen; Kraus, Andre; Skoczynski, Kathrin; Schiffer, Mario; Krüger, René; Naas, Stephanie; Schödel, Johannes; Buchholz, Björn (Royal Society Open Science, 2023)
Mutations in polycystin-1 which is encoded by the PKD1 gene are the main causes for the development of autosomal dominant polycystic kidney disease. However, only little is known about the physiological function of polycystin-1 and even less about the regulation of its expression. Here, we show that expression of PKD1 is induced by hypoxia and compounds that stabilize the hypoxia-inducible transcription factor (HIF) 1α in primary human tubular epithelial cells. Knockdown of HIF subunits confirms HIF-1α-dependent regulation of polycystin-1 expression. Furthermore, HIF ChIP-seq reveals that HIF interacts with a regulatory DNA element within the PKD1 gene in renal tubule-derived cells. HIF-dependent expression of polycystin-1 can also be demonstrated in vivo in kidneys of mice treated with substances that stabilize HIF. Polycystin-1 and HIF-1α have been shown to promote epithelial branching during kidney development. In line with these findings, we show that expression of polycystin-1 within mouse embryonic ureteric bud branches is regulated by HIF. Our finding links expression of one of the main regulators of accurate renal development with the hypoxia signalling pathway and provides additional insight into the pathophysiology of polycystic kidney disease.
CRIS-Team Scopus Importer:2023-06-30
Keywords: hypoxia; hypoxia-inducible factor; kidney development; PKD1; polycystic kidney disease; transcription regulation

Nieren- und Harnwegstumore - Naas, Stephanie; Kunath, Frank; Schödel, Johannes (Geriatrische Nephrologie, 2023)
Die Inzidenzen von Nieren- und Harnwegstumoren steigen mit dem Lebensalter stetig an. Diese Erkrankungen betreffen damit insbesondere ein Patientenkollektiv, das sich durch vermehrte Komorbiditäten, psychosoziale Einschränkungen und eine Reduktion an Selbstständigkeit auszeichnet. Hieraus ergeben sich Herausforderungen, die durch eine adäquate Therapiesteuerung adressiert werden müssen. Beide Tumorentitäten sind in lokal begrenzten Frühstadien durch eine operative Sanierung kurativ therapierbar. Die Eignung der Patienten für eine chirurgische Therapie sollte jedoch unter Berücksichtigung der Vorerkrankungen, der perioperativen Risiken sowie der Lebensqualität individuell festgelegt werden. Auf diese Weise können Patienten identifiziert werden, die von alternativen, weniger invasiven Behandlungsmethoden profitieren. In Hinblick auf die Therapie fortgeschrittener Stadien haben sich durch die Zulassung der Checkpointinhibitoren neue Therapieoptionen ergeben, die im Besonderen für Patienten geeignet sind, die nicht chemotherapiefähig sind. Zusammenfassend erscheint eine individualisierte Therapieplanung auf Basis eines interdisziplinären Tumorboardbeschlusses unter Einbeziehung der Lebensumstände sowie des Patientenwunsches äußerst sinnvoll.

The renal cancer risk allele at 14q24.2 activates a novel hypoxia-inducible transcription factor-binding enhancer of DPF3 expression - Protze, Johanna; Naas, Stephanie; Krüger, René; Stöhr, Christine; Kraus, Andre; Grampp, Steffen; Schiffer, Mario; Hartmann, Arndt; Wullich, Bernd; Schödel, Johannes; Wiesener, Michael (Journal of Biological Chemistry, 2022)
Evolution of clear cell renal cell carcinoma is guided by dysregulation of hypoxia-inducible transcription factor (HIF) pathways following loss of the von Hippel-Lindau tumor suppressor protein. Renal cell carcinoma (RCC)-associated polymorphisms influence HIF–DNA interactions at enhancers of important oncogenes thereby modulating the risk of developing renal cancer. A strong signal of genome-wide association with RCC was determined for the single nucleotide polymorphism (SNP) rs4903064, located on chr14q.24.2 within an intron of DPF3, encoding for Double PHD Fingers 3, a member of chromatin remodeling complexes; however, it is unclear how the risk allele operates in renal cells. In this study, we used tissue specimens and primary renal cells from a large cohort of RCC patients to examine the function of this polymorphism. In clear cell renal cell carcinoma tissue, isolated tumor cells as well as in primary renal tubular cells, in which HIF was stabilized, we determined genotype-specific increases of DPF3 mRNA levels and identified that the risk SNP resides in an active enhancer region, creating a novel HIF-binding motif. We then confirmed allele-specific HIF binding to this locus using chromatin immunoprecipitation of HIF subunits. Consequentially, HIF-mediated DPF3 regulation was dependent on the presence of the risk allele. Finally, we show that DPF3 deletion in proximal tubular cells retarded cell growth, indicating potential roles for DPF3 in cell proliferation. Our analyses suggest that the HIF pathway differentially operates on a SNP-induced hypoxia-response element at 14q24.2, thereby affecting DPF3 expression, which increases the risk of developing renal cancer.
CRIS-Team Scopus Importer:2022-03-18